2021
DOI: 10.1136/annrheumdis-2021-eular.2976
|View full text |Cite
|
Sign up to set email alerts
|

Pos0225 risk of Major Cardiovascular Event Across Jak Inhibitor Treated Patients: Analysis of a National Claim Database

Abstract: Background:Inhibiting a specific JAK may impede more than one pathway, explaining both the efficacy and adverse effects observed with JAK inhibitors (JAKi). Among those, there have been recent concerns about potential thromboembolic risks with these drugs. As patients enrolled are not representative of all patients who may receive JAKi, data from trials are unlikely to provide definitive answers. Real impact of JAKi in real life on major cardiovascular events is not known.Objectives:To evaluate the risk of ven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…This risk faded 1 month following exposure. 7 Conversel, the SELECT phase III clinical programe (5 randomized controlled trials) for rheumatoid arthritis found no difference in the rate of venous thromboembolic events among patients receiving upadacitinib, methotrexate, or adalimumab. 8 When comparing the findings of the post hoc analysis 7 to those of the SELECT phase III trial, 8 we may suggest that upadacitinib seems to have a better cardiovascular safety profile relative to baricitinib and tofacitinib.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This risk faded 1 month following exposure. 7 Conversel, the SELECT phase III clinical programe (5 randomized controlled trials) for rheumatoid arthritis found no difference in the rate of venous thromboembolic events among patients receiving upadacitinib, methotrexate, or adalimumab. 8 When comparing the findings of the post hoc analysis 7 to those of the SELECT phase III trial, 8 we may suggest that upadacitinib seems to have a better cardiovascular safety profile relative to baricitinib and tofacitinib.…”
Section: Discussionmentioning
confidence: 99%
“… 7 Conversel, the SELECT phase III clinical programe (5 randomized controlled trials) for rheumatoid arthritis found no difference in the rate of venous thromboembolic events among patients receiving upadacitinib, methotrexate, or adalimumab. 8 When comparing the findings of the post hoc analysis 7 to those of the SELECT phase III trial, 8 we may suggest that upadacitinib seems to have a better cardiovascular safety profile relative to baricitinib and tofacitinib. This could explain why our patient, while having a strong cardiovascular disease risk profile, was tolerating upadacitinib so well without suffering any venous thromboembolic events or adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…15,16,18 MACE and herpes zoster (HZ) have been reported to be associated with other JAKi treatments; however, the incidence rates for these events are similar to placebo (Table 4). 16,19,[37][38][39][40] RA patients were eligible to enroll in the LTE FINCH 4 study if they had completed 1 of the FINCH parent studies. Among patients who were MTX-IR and were rerandomized for the LTE from ADA + MTX to filgotinib + MTX or those who continued their parent-trial treatment with filgotinib 100 or 200 mg with MTX, incidence of TEAEs, serious AEs (SAEs), and ≥3-grade AEs were largely comparable (Table 5).…”
mentioning
confidence: 99%
“…The first real-life experience with baricitinib, showing an increased risk of VTE in patients with cardiovascular risk factors may support this statement. 22,23 However, although the mechanisms of action are similar between JAKis, JAK selectivity may change the safety profile according to the JAK isoform targeted. An example might be the potential contribution of JAK2 in the occurrence of VTE.…”
mentioning
confidence: 99%